Two RNA-binding proteins mediate the sorting of miR223 from mitochondria into exosomes - Liang Ma; Jasleen Singh; Randy Schekman (eLife, 2023)
Fusion of multivesicular bodies (MVBs) with the plasma membrane results in the secretion of intraluminal vesicles (ILVs), or exosomes. The sorting of one exosomal cargo RNA, miR223, is facilitated by the RNA-binding protein, YBX1 (Shurtleff et al., 2016). We found that miR223 specifically binds a ‘cold shock’ domain (CSD) of YBX1 through a 5’ proximal sequence motif UCAGU that may represent a binding site or structural feature required for sorting. Prior to sorting into exosomes, most of the cytoplasmic miR223 resides in mitochondria. An RNA-binding protein localized to the mitochondrial matrix, YBAP1, appears to serve as a negative regulator of miR223 enrichment into exosomes. miR223 levels decreased in the mitochondria and increased in exosomes after loss of YBAP1. We observed YBX1 shuttle between mitochondria and endosomes in live cells. YBX1 also partitions into P body granules in the cytoplasm (Liu et al., 2021). We propose a model in which miR223 and likely other miRNAs are stored in mitochondria and are then mobilized by YBX1 to cytoplasmic phase condensate granules for capture into invaginations in the endosome that give rise to exosomes.